Application of Divide and Conquer Extended Genetic Algorithm to Tertiary Protein Structure of Chymotrypsin Inhibitor-2. Issue 4 (8th July 2010) - Alfaro, A.; Doan, M.; Finke, J.; Galdes, M.; Zohdy, M.
Abstract : Determining the method by which a protein thermodynamically folds and unfolds in three-dimension is one of the most complex and least understood problems in modern biochemistry. Misfolded proteins have been recently linked to diseases including Amyotrophic Lateral Sclerosis and Alzheimer's disease. Because of the large number of parameters involved in defining the tertiary structure of proteins, based on free energy global minimisation, we have developed a new Divide and Conquer (DAC) Extended Genetic Algorithm. The approach was applied to explore and verify the energy landscape of protein chymotrypsin inhibitor-2.